The Use of Audio-Visual Media to Improve Learning Outcomes of Fourth-Grade Students in Pancasila Education - Juwita, Selvy Ayu; Apriani, Ria; Hotnida, Denny (CV Media Inti Teknologi, 2024)
This study aims to improve the learning outcomes of fourth-grade students in Pancasila Education through the use of Audio-Visual media at SD Negeri 37 Bengkulu. This research is a Classroom Action Research (CAR), conducted in four stages: planning, implementation, observation, and reflection. The research subjects were 28 fourth-grade students. Three data collection techniques were employed: observation, documentation, and tests. The results showed an improvement in student learning outcomes and positive student responses. Student learning outcomes increased significantly. In the pre-cycle stage, the student mastery percentage was 42.86%, with 12 students achieving mastery. In the first cycle, the percentage of student mastery increased to 71.43%, with 20 students achieving mastery, and in the second cycle, the percentage of student mastery nearly reached perfection, at 92.86%, with 26 out of 28 students achieving mastery. This indicates that the application of audio-visual media can enhance student learning outcomes in Pancasila education.